QUANTIFICATION OF THE EFFECTS OF THE INLET WAVEFORM ON HEMODYNAMICS INSIDE INTERNAL CAROTID ARTERIES USING COMPUTATIONAL FLUID DYNAMICS. (Sciences & Technologie. B, Sciences de l'ingénieur, 2017)
Hemodynamics is an important bio-mechanic factor, which is implicated in the regulation and regeneration function inside the vessels. However, disturbing in its factors may cause development of many vascular diseases. Computational fluid dynamics (CFD) is alternative tool, which is used to assess hemodynamic factors inside complex cerebral vessels.The purpose of this study is to assess the influence of the inlet waveforms under the same mean inflow on different hemodynamic factors inside Internal Carotid Arteries (ICA), using computational fluid dynamics combined to patient specific MRI images.Four numerical models of (ICA) were reconstructed from 3D TOF MRI images. Navies-Stokes equations were solved inside the geometry using finite elements method. Sixteen simulations using four-inlet waveforms and four ICA arteries were performed to quantify the influence of the inlet waveform on blood flow inside ICA.Varying the Inlet waveform boundary conditions has important effects on the overall instantaneous hemodynamic factors assessed on the geometries. However, time averaged factor assessed has been constant for individual cases.Information about patient-specific inlet waveform is necessary for the accuracy of the patient-specific computation.